Effects of Par-Frying and Calcium Propionate on the Quality of Frozen Curry Puff - Hussain, Norhayati; Ishak, Izzreen; Syafizan Rosle, Nurul; Husna Mohamed, Nurul; Abd Ghani, Maaruf (International Journal of Engineering and Technology, 2019)
This study proves that the application of par-frying method and addition of calcium propionate able to prolong the shelf life and preserve the quality of frozen pastry curry puff during distribution and storage after exposure to fluctuating temperature. Par-fried curry puff added with 0.1% calcium propionate produce lower moisture content, oil uptake and weight loss than non-par fried puff. In addition, par fried curry puff was capable of preventing any visible black spots (after 4 weeks storage) which are related to the quality defect. No sensorial changes detected during sensory evaluation in terms of texture, appearance, taste and overall acceptability after addition of calcium propionate. There is a high possibility of frozen curry puff to be commercialized internationally without any deterioration.Â Â Â